2000
DOI: 10.1002/1098-2280(2000)35:4<343::aid-em9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin induces cytogenetic damage in the early life stages of the marine mussel,Mytilus edulis

Abstract: Using an integrated approach, the genotoxic potential of bis(tri‐n‐butyltin), an antifouling agent known to disrupt endocrine system in marine invertebrates, has been evaluated in the embryo‐larval stages of the edible mussel, Mytilus edulis. While evaluating the genotoxic potential, the toxicity of tributyltin was also taken into account by determining the maximum tolerated dose. The study suggested that tributyltin is capable of inducing cytogenetic damage (sister chromatid exchanges and chromosomal aberrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In addition to effects on the internal defence system, Jha et al (2000) found genotoxic effects of TBT on embryo-larval stages of M. edulis (sister chromatid exchanges and chromosomal aberrations). A conclusive example linking genetic damage with perturbation of endocrine function and adverse effects in vivo was provided by Hagger et al (2006).…”
Section: Antiandrogensmentioning
confidence: 98%
“…In addition to effects on the internal defence system, Jha et al (2000) found genotoxic effects of TBT on embryo-larval stages of M. edulis (sister chromatid exchanges and chromosomal aberrations). A conclusive example linking genetic damage with perturbation of endocrine function and adverse effects in vivo was provided by Hagger et al (2006).…”
Section: Antiandrogensmentioning
confidence: 98%
“…Following optimization and validation of the assays using the reference chemicals, the concentration range of arsenicals was selected based on earlier in vitro studies using human cells [Jha et al, 1992]. Again, the range of concentrations was slightly modified to fit a semi-logarithmic scale (i.e., 1, 3.2, and 10 M), as adopted in our earlier in vivo studies using early life stages of marine invertebrates [e.g., Jha et al, 2000]. Stock solutions of the arsenicals were prepared in culture media (without serum) and directly added to the culture flasks.…”
Section: Concentrations Of Reference Agents and Arsenicalsmentioning
confidence: 99%
“…TBT increases the mortality of Crassostrea gigas embryos at 0.36 µg/L at 24 h (Tsunemasa et al, 2011), and induces malformations of Mytilus galloprovincialis embryos at 0.161 µg/L (Beiras and Bellas, 2008). TBT also induces cytogenetic damage (sister chromatid exchanges and chromosomal aberrations) in Mytilus edulis embryo (Jha et al, 2000).…”
Section: Bivalvesmentioning
confidence: 99%